Evaluation of surface quality of some Malaysian species as function of outdoor exposure - Salim, Hiziroglu; Uyup, Mohd Khairun Anwar; Hussain, Hamdan; Md. Tahir, Paridah (2007)
In this study influence of outdoor exposure on surface quality of five Malaysian species, Merbau (Intsia palembanica), dark red meranti (Shorea spp.), balau (Shorea spp.) keranji (Dialium spp.), and keruing (Dipterocarpus spp.) were evaluated. Surface roughness of the samples exposed to outdoor environment ranging from 1 week to 4 weeks were determined using a stylus type equipment. Three roughness parameters average roughness (Ra), mean peak-to-valley height (Rz), and maximum roughness (Rmax) calculated from the surface profiles of the samples employing a profilometer were used for the analyses. Control samples of keranji had the smoothest surface with an average Ra value of 3.90 μm while keruing had the roughest surface with 8.20 μm among five species. None of the samples from five different species resulted in significant differences in roughness values within 1-week interval during the outdoor exposure at 95% confidence level. Roughness measurements taken from the surface of control samples and samples exposed for 4-week outdoor from belau, keruing, and dark red meranti showed significant difference at 95% confidence level. These differences were not significant in the case of merbau and keranji. Based on the findings from this study it appears that stylus method can be used to evaluate surface quality of various tropical species as function of outdoor exposure.